If it's not what You are looking for type in the equation solver your own equation and let us solve it.
26=c/23
We move all terms to the left:
26-(c/23)=0
We add all the numbers together, and all the variables
-(+c/23)+26=0
We get rid of parentheses
-c/23+26=0
We multiply all the terms by the denominator
-c+26*23=0
We add all the numbers together, and all the variables
-1c+598=0
We move all terms containing c to the left, all other terms to the right
-c=-598
c=-598/-1
c=+598
| 29+20=5a+6 | | 191=m+254 | | (2x+11)°=(6x–7)° | | 1/18x-5/7=3/4 | | 6x+20=8x–16 | | 14h=-112 | | 13x-40=50 | | 6(c−13)=−12 | | -28=w-17 | | -8(u+5)=-6u-26 | | —32=4t | | 4x-11=-29 | | x/20=1/10 | | 728=-26w | | 728=-26q | | 7|6x-6|=21 | | 2x-1+5x-13=180 | | x/85=-125 | | 1+2x-1+5x-13=180 | | x/5=13/5 | | 2{p+1}=16 | | 2{p+1}=17 | | −2(−4x+1)=5 | | 2y−–8=12 | | 75+36+x=250 | | X1f9(2-)=3 | | P=13+8d/13 | | –6+4q=6 | | n/2=3/9 | | X1f9(2-1)=3 | | 11+4x=22.5 | | 3^(4x-1)-5^(2x)=0 |